Prophylactic supplementation of phosphate, magnesium, and potassium for the prevention of refeeding syndrome in hospitalized individuals with anorexia nervosa. (14th October 2021) - Gallagher, Donna; Parker, Anna; Samavat, Hamed; Zelig, Rena
Abstract: Medical stabilization, nutrition rehabilitation, and weight restoration, while minimizing risk for the potentially fatal complication of refeeding syndrome, are the primary goals for the treatment of hospitalized individuals with anorexia nervosa and other restrictive‐type eating disorders. The purpose of this review was to examine the literature exploring the prophylactic supplementation of phosphate, magnesium, and potassium, in addition to routine thiamin and multivitamin supplementation, for the prevention of refeeding syndrome in adolescents and adults with anorexia nervosa. Through evaluation of outcomes (including serum electrolyte levels and clinical signs and symptoms such as respiratory failure, cardiac failure, peripheral edema, rhabdomyolysis, and encephalopathy), three studies found that prophylactic supplementation of potassium, magnesium, and/or phosphate were effective in preventing refeeding syndrome or refeeding hypophosphatemia (a characteristic of refeeding syndrome). Although all studies found that prophylactic supplementation was effective in preventing refeeding syndrome, refeeding approaches (including the method, amount, and duration of nutrient delivery) as well as the populations studied varied considerably, making it difficult to arrive at specific recommendations for practice. Randomized controlled trials are needed to further examine the safety and effectiveness of prophylactic supplementation of phosphate, magnesium, and potassium on the prevention of refeeding syndrome, utilizing similar feeding and supplementation protocols.